ARabic-Kafa: Design and Development of Educational Material for Arabic Vocabulary with Augmented Reality Technology - Daud, Wan Ab Aziz Wan; Ghani, Mohammad Taufiq Abdul; Rahman, Ahmad Abdul; Yusof, Mohd Akashah Bin Mohamad; Amiruddin, Ahmad Zaki (The journal of language and linguistic studies, 2021)
This research focuses on the production and creation of educational materials for Arabic vocabulary learning using Augmented Reality Technology, namely ARabic-Kafa, which can support both teachers and students. The Marker Based Tracking tool is used in this Augmented Reality application. This method was employed because it can read objects and then display 3-dimensional (3D) virtual objects. The first step in resolving this issue is to create animations through the blender application, choose the image to be utilised as a Marker, and finally, export it to Vuforia to form an Augmented Reality app. The mobile app of Augmented Reality-based educational media is the product of this research. A series of testing were employed and a minimum distance for displaying a 3D object is 10 cm, and the minimum angle 30° to 90° to view 3D objects. The rotation marker's output effectively shows every aspect of the 3D object. Furthermore, the audio pronunciations can be played effortlessly.